A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMKN 2 PEKANBARU IN COMPREHENDING PROCEDURE TEXTS - Giawa, Christina; Azhar, Fadly; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The aim of this study is to find out the ability of the second year students of SMKN 2 Pekanbaru in comprehending procedure texts. The population of this research is all of the second year students which consisted of 301 students. There were 40 students who participated in this study as sample. The instrument was a test adapted from authentic material. The frame of the test was covered by 5 components such as, finding main idea, finding factual information, finding meaning of difficult word, finding references, and finding generic structure. Each component consisted of 6 questions. The test contained 30 items. Before the test was administered, the test was tried out to find out the difficulty level and the reliability of the test. To analyze the data, the raw score of the students was calculated and the level of ability was identified by using the classification of ability level by Harris (1974). The result showed that the ability of the second year students of SMKN 2 Pekanbaru in comprehending procedure texts was at Mediocre level with mean score 51.8. Therefore, it can be concluded that most of the students were able to comprehend procedure texts. To reach this, the students were suggested to do more practice in reading procedure texts in order to comprehend and to improve the ability in reading due to the poorness of their reading ability.Key Words : Reading Ability, Reading Comprehension, Procedure Text